2019
DOI: 10.1111/imj.14259
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function during exacerbations of chronic obstructive pulmonary disease

Abstract: Background The reported prevalence of cognitive impairment in patients with stable chronic obstructive pulmonary disease (COPD) ranges 36‐77%. Few studies report the prevalence of cognitive impairment in acutely unwell COPD patients. Aims To determine the prevalence and time course of cognitive impairment in patients with COPD during and after an admission to hospital with an exacerbation of the disease. Methods Patients admitted to hospital with an exacerbation of COPD between October 2013 and November 2014 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Dodd et al [11] also found no improvement in cognitive performance at 3-months post-discharge using a comprehensive neuropsychological assessment. However, there are inconsistencies in methodology across studies and, as such, other studies have shown an improvement in cognition following recovery [15,17,18]. These methodological differences make direct comparisons between studies difficult, as the timings of the baseline assessment (e.g.…”
Section: Recovery In Patients Following Aecopdmentioning
confidence: 99%
See 3 more Smart Citations
“…Dodd et al [11] also found no improvement in cognitive performance at 3-months post-discharge using a comprehensive neuropsychological assessment. However, there are inconsistencies in methodology across studies and, as such, other studies have shown an improvement in cognition following recovery [15,17,18]. These methodological differences make direct comparisons between studies difficult, as the timings of the baseline assessment (e.g.…”
Section: Recovery In Patients Following Aecopdmentioning
confidence: 99%
“…Differences observed in other studies may be related to the assessment of cognitive function soon after hospital admission. Poot et al [18] and Lopez-Torres et al [17] saw a significant improvement in cognition following a 6-8-week and 1-month recovery, respectively, but both baselines were taken during time of exacerbation. By aligning our baseline assessment of cognition with the approximate timing of PR offer, the present study found that mild-moderate cognitive impairment should not be considered as a reason to delay the offering to the post-discharge phase.…”
Section: Recovery In Patients Following Aecopdmentioning
confidence: 99%
See 2 more Smart Citations
“…During acute exacerbations patients with COPD have been found to have worse cognitive impairment than similar patients with acute heart failure [17]. This acute cognitive deterioration is seen to improve over 6 weeks in most, but not in all patients [18]. Whether exacerbations change cognition in the long term is unclear [19].…”
Section: Hypothesis For Mechanism Linking Copd With Cognitive Impairmentmentioning
confidence: 99%